Examination of Teaching and Learning Processes of an Elective Applied Mathematics Course - Özlem ALBAYRAKOĞLU; Abdurrahman KILIÇ (Anı Publishing, 2021)
This study aimed to examine the teaching and learning processes of an Elective Applied Mathematics course according to the opinions of mathematics teachers and students. Data was collected through interviews and focus group interviews, and the content analysis method was performed to interpret data. Results revealed that the requirements of the curriculum and student-centered education approach were generally not fulfilled. Therefore, meeting student expectations was not at the desired level. However, some teachers expressed that enriching the course with mathematical modeling and engaging problems would affect students' attitudes towards mathematics, in line with the general idea of the course. In general, the lack of school resources and limited teaching staff was a problem that restrict the instruction. As a recommendation, Elective Applied Mathematics teachers and students should be informed about the aim of the course. Moreover, teachers should be experienced in mathematical modeling.